Transformasi Institusi Pelaksana Wakaf: Kes Waqaf An-Nur Corporation - Mahmood, Nurul Asykin; Markom, Ruzian (Universiti Sains Islam Malaysia, 2024)
The role and contribution of waqf institutions in the nation's socioeconomic development has been proven. Al-Azhar University, for example continue to operate through the application waqf until now. Recognizing the importance of waqf in the current life and the acquisition of reward is prolonged due to waqf systematically implemented and structured. Although, the management and administration of waqf is not a new issue to be discussed, the implementation is still more traditional. This problem should be resolved immediately. In line with the expansion of the global economy, waqf should be transformed in terms of management and administration of waqf institutions to improve the efficiency and effectiveness leading to the advancement of the country in general. Therefore, this study aimed to identify the participating institutions and the role of waqf in Malaysia mutawalli. The study found that the Waqf An-Nur Corporation (WANCorp) managed to transform institutions implementing parallel with the development of waqf contemporary nature. Thisdescriptive study done through the acquisition of information from books, theses, journals and proceedings of the seminar and the website. Thus, the findings are expected to help boost efforts to transform the participating institutions.